(3MOGFb GdfGXQIs - (3GdOQGRj GdHMQGf, GHf YUahQ, jhSa Hf CMeO Hf EHQGgje, J(B1186(3g`s ((3MSjf Hf MSf GdNWjs)
(3ChdgG (B:s
(3HSe Gddg (B.. (3GdaUd GdMGOj YTQ aj HjY GdZQhQ hGdeLGRaI hajg eSGFd GdeSCdI GdChdi bGd GdTjN aj GdfgGjI ef GTJQi TjFGHMce faSg hde jPcQ GdKef HYjfg cGf GdHjY HGWdG aEf gdc aj jO GdeHJGY cGf Ydjg bjeJg jhe GHJjGYg (B...s
(3BNQgG (B:s
... (3GdKGfj bGdhG dh HOd UGMH GdCQV ddaGQS bjeI GdaQS ajchf GdaQS dg HCf jHjYg EjGg de jLH Ydi UGMH GdaQS GdbHhd hcPG dh OaY GdaGQS dUGMH GdCQV CLQI CQVg (B... (3Je cJGH GdJLGQI hjJdhg cJGH GdhOjYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8/215s
(3GdPQjYI (B6/208 (1557)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis